Dinamika Sosial dan Ekonomi Buruh Perempuan di Perkebunan Teh PT Pecconina Baru (1988-2021) - Sapmita, Resi Dwi; Syafrizal, Syafrizal (Analisis Sejarah, 2025)
This study analyses the changing working conditions and socio-economic impacts on female labourers at the PT Pecconina Baru tea plantation between 1988 and 2021. Employing historical methodology—including heuristics, source criticism, interpretation, and historiography—the study examines the shift in women’s roles from the domestic sphere to the public domain as plantation workers. The findings reveal that, initially, female labourers worked as informal daily workers with low wages and no social security. Over time, they gained access to facilities such as transportation and children’s education. Although wages remained limited, this employment provided economic stability and the opportunity to contribute to household income. Some workers experienced upward social mobility through job promotions, their children’s educational advancement, and improvements in household assets. The study highlights that women's labour in the plantation sector represents not only exploitation but also opportunities for economic empowerment. In certain contexts, women demonstrated their capacity to adapt and improve their well-being through persistence and active participation in the available labour system. The academic contribution of this research lies in mapping the intersection of gender, labour, and social mobility within the agrarian sector. The findings challenge the singular narrative of female powerlessness in plantation work and underscore the importance of policies that promote protection, fair wages, and access to social services for female labourers. Thus, this study offers a new perspective on the dynamics of women's labour and structural transformation in rural economies.